MANAGEMENT OF ISLAMIC EDUCATION INSTITUTIONS BASED ON RELIGIOUS MODERATION - Albantani, Azkia Muharom; Mustaqim, Mustaqim; Akmalia, Wilda (The Ministry of Religious Affairs, The Republic of Indonesia, 2022)
Islamic educational institutions must have excellent human resources, which are not only limited to human resources from their own country, but also must be able to compete with human resources from foreign countries. Improving the management of Islamic educational institutions is a must for the leaders of Islamic educational institutions to face more complex changes in the future. The purpose of writing this policy paper is to encourage the inception of a foundation for the management of Islamic education institutions based on religious moderation to create a moderation in students' religious attitudes. This policy paper is based on the results of research conducted by the Education Research Team in 2022. This research uses a qualitative method with a literature review approach. The management of Islamic educational institutions at the tertiary level based on religious moderation needs to be directed to achieve the strategic plan of the Ministry of Religious Affairs of the Republic of Indonesia. The recommended alternative policies are first, the Ministry of Religious Affairs needs to formulate a new policy regarding operational guidelines for the management of Islamic education institutions at the elementary, secondary, and tertiary levels based on religious moderation in detail. Second, the Ministry of Religious Affairs needs to formulate a new policy in collaboration with related educational institutions in the framework of implementing religious moderation in institutional management.